Proceedings of the ACM Symposium on Applied Perception 2016
DOI: 10.1145/2931002.2931003
|View full text |Cite
|
Sign up to set email alerts
|

Action coordination with agents

Abstract: We investigated how people jointly coordinate their decisions and actions with a computer-generated character (agent) in a largescreen virtual environment. The task for participants was to physically cross a steady stream of traffic on a virtual road without getting hit by a car. Participants performed this task with another person or with a computer-generated character (Fig.1). The character was programmed to be either safe (taking only large gaps) or risky (also taking relatively small gaps). We found that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…One interpretation proposes that the participants might have felt trapped within the high density crowd once they were exposed to it. Thus, the participants may have decided to move with the flow of the crowd instead of attempting to free themselves from it, 32,43 as prior studies have shown that humans tend to coordinate with virtual characters when in their presence 46‐48 . Moreover, the direction and speed interaction effect suggests that our participants may have been more willing to follow the virtual crowd when it was moving at a low rather than a high speed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One interpretation proposes that the participants might have felt trapped within the high density crowd once they were exposed to it. Thus, the participants may have decided to move with the flow of the crowd instead of attempting to free themselves from it, 32,43 as prior studies have shown that humans tend to coordinate with virtual characters when in their presence 46‐48 . Moreover, the direction and speed interaction effect suggests that our participants may have been more willing to follow the virtual crowd when it was moving at a low rather than a high speed.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have investigated the movement coordination of participants. Such studies have included real 40‐42 and virtual reality 43‐45 scenarios in which people coordinated their movements while crossing an intersection in the presence of either a human or virtual character. It has been found 46‐48 that two humans tend to become more sensitive to each other's presence and to simultaneously change their decisions or actions when crossing a road as part of a group, compared with when doing so on their own.…”
Section: Related Workmentioning
confidence: 99%
“…The results of this investigation also add to a growing body of literature on joint road crossing and joint action more generally Jiang et al, 2016;O'Neal, Jiang, Brown, Kearney, & Plumert, 2019). Judging gap affordances is more complicated when acting with another person because decisions must consider the action capabilities of both people.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have investigated the movement coordination of participants. Such studies included real 32‐34 and virtual reality 1,35,36 scenarios with people coordinating their movements while crossing an intersection in the presence of either a human or a virtual character. A series of studies 37‐39 found that two humans tended to become more sensitive to the each other's presence.…”
Section: Related Workmentioning
confidence: 99%